MANAJEMEN PRIVASI DALAM APLIKASI TANTAN (Kajian Gendered Criteria dalam Teori Communication Privacy Management) - Anis Endang Sri Murwani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
This study aims to examine how private information is disclosed and withheld in the chat feature of Tantan application, especially based on the Gendered-Criteria factor. The theory used in this research is Communication Management Privacy Theory - Sandra Petronio. This is a descriptive qualitative research. Data were collected through interviews with four informants, consisting of two women and two men who are in the young adulthood age category.The results of the study found that Tantan application users have good privacy management because they carry out privacy management by enforcing strict rules in choosing co-owners for their privacy. Some of the strict rules are: not telling privacy (information about family) to friends found on the Tantan application and only telling it to people who are truly trusted. In relation to the Rule-based Management System based on gender criteria, men are more trusted in maintaining privacy secrets, but there is no difference in privacy disclosure between women and men.